2015
DOI: 10.1111/dar.12343
|View full text |Cite
|
Sign up to set email alerts
|

Co‐ingestion of energy drinks with alcohol and other substances among a sample of people who regularly use ecstasy

Abstract: Co-ingestion of EDs with licit and illicit drugs is common among people who regularly use ecstasy and related drugs. Adverse outcomes of co-ingestion suggest that targeted education regarding negative interactive drug effects is crucial for harm reduction. [Peacock A, Sindicich N, Dunn M, Whittaker E, Sutherland R, Entwistle G, Burns L, Bruno R. Co-Ingestion of Energy Drinks with Alcohol and Other Substances among a Sample of People Who Regularly Use Ecstasy. Drug Alcohol Rev 2016;35:352-358].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…No significant differences were found between the groups regarding demographics or alcohol and drug use, alcohol consumption on AMED sessions, and AMED consumption‐related risk taking. Finally, Peacock et al () examined the motives for AMED consumption of 693 Australian ecstasy users. Participants reported consuming AMED to increase alertness (59%), for the taste (25%), to party for longer (23%), and to combat fatigue (16%).…”
Section: Resultsmentioning
confidence: 99%
“…No significant differences were found between the groups regarding demographics or alcohol and drug use, alcohol consumption on AMED sessions, and AMED consumption‐related risk taking. Finally, Peacock et al () examined the motives for AMED consumption of 693 Australian ecstasy users. Participants reported consuming AMED to increase alertness (59%), for the taste (25%), to party for longer (23%), and to combat fatigue (16%).…”
Section: Resultsmentioning
confidence: 99%
“…Since the last meta-analysis [82] another study has been published [78] assessing the effects of AmED on attentional and working memory. Like in previous studies, mutual antagonism was not evident in all tasks and depended on alcohol and ED dose, and the blood alcohol limb [85]. The most recent studies [86,87] assessed the effects of AmED on driving-related skills, and showed that EDs increase willingness to drive while drunk, but did not, or only partially counteract alcohol effects on objective performance outcomes.…”
Section: Interactions With Energy Drinksmentioning
confidence: 57%
“…Published cases of intoxication with EDs have been screened to identify the substances most concomitantly consumed and the reported effects. The main characteristics of each case report are summarized in Table 3 for combination with alcohol [89][90][91][92][93] and Table 4 for combination with other drugs of abuse [1,16,33,85,88,[94][95][96][97]. Intake of more than three cans of EDs, or less in poor tolerance individuals, can lead to caffeine intoxication [14].…”
Section: Intoxications With Eds and Managementmentioning
confidence: 99%
“…Energy drink use has been found to be a common co-ingestant among those using both alcohol and other stimulants (i.e., ecstasy) for the purposes of energy enhancement. 12,13 In this patient case, he presented with the consumption of both an opioid, an energy drink, and a psychostimulant within a similar time frame, and although he displayed no symptoms suggestive of respiratory depression on his initial visit, this was possibly suppressed by his stimulant coingestion. The time course of his initial presentation, his reported inability to sleep that night, followed by an apneic episode in the afternoon following day, approximates the elimination rate of extended-release dextroamphetamine and amphetamine.…”
Section: Discussionmentioning
confidence: 89%
“…11 Energy drink use has also been noted to be frequent among those that use alcohol, ecstasy, and amphetamines, most commonly for the reported purpose of increasing alertness. 12,13 Case Report A 26-year-old male (83.9 kg) whose only relevant past medical history consists of occasional recreational dextroamphetamine/amphetamine use presented to the ED approximately 1 h after unintentionally ingesting 20-25 mL (200-250 mg) of liquid methadone (Figure 1). Patient stated that he took his brother's methadone (5 mL daily) by accident, who is in a methadone program and prefers to mix his methadone with an energy drink in the same bottle, of which 4-5 days' worth was remaining.…”
Section: Introductionmentioning
confidence: 99%